IMPROVING STUDENTS‘ ABILITY IN LISTENING TO A RECOUNT GENRE THROUGH SONG ANALYSIS TECHNIQUE - Zarwin . (Universitas Bengkulu, 2016)
This research was conducted to improve IX A grade students’ ability in listening to recount genre. In doing this research the researcher applied analyzing song technique. There were 32 students involved in this research. The data of this research was taking in two ways; test and observation. In taking the observation data the researcher was helped by two English teachers to know how far that the teaching process worked. The test was used to know the students progress from cycle to cycle. The test result showed that in the cycle one there are 41.25 % students still had problem with the grammar, 38.78% students still had problem with the spelling and 31.87% students had problem in area of hearing, while the average score of the student’s achievement is 61.00. In the cycle two the students made improvement significantly. There were only 25.00% students still had problem with the grammar, 23.00% students had problem with spelling and 27.19% students had problem with hearing, and the average score of the students’ achievement was 75.00. from the result it can be concluded that song analysis technique can improve the IXA Grade students ability in listening to a recount genre